Investigation of dyslexia and SLI risk variants in reading- and language-impaired subjects - Newbury, D; Paracchini, S; Scerri, T; Winchester, L; Addis, L; Richardson, A; Walter, J; Stein, J; Talcott, J; Monaco, A (Springer, 2011)
Dyslexia (or reading disability) and specific language impairment (or SLI) are common childhood disorders that show considerable co-morbidity and diagnostic overlaps and have been suggested to share some genetic aetiology. Recently, genetic risk variants have been identified for SLI and dyslexia enabling the direct evaluation of possible shared genetic influences between these disorders. In this study we investigate the role of variants in these genes (namely MRPL19/C20RF3, ROBO1, DCDC2, KIAA0319, DYX1C1, CNTNAP2, ATPsC2 and CMIP) in the aetiology of SLI and dyslexia. We perform case-control and quantitative association analyses using measures of oral and written language skills in samples of SLI and dyslexic families and cases. We replicate association between KIAA0319 and DCDC2 and dyslexia and provide evidence to support a role for KIAA0319 in oral language ability. In addition, we find association between reading-related measures and variants in CNTNAP2 and CMIP in the SLI families.